Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

HELP MATH 100 POINTS HELP US

HELP MATH 100 POINTS HELP US class=

Sagot :

Question↷

Which statement best reflects the solution(s) of the equation?

[tex] \small \sqrt{2x - 1} - x + 2 = 0[/tex]

Answer↷

There is only one solution: x = 5 .

The solution x = 1 is an extraneous solution.

Solution↷

[tex] \small \sqrt{2x - 1} - x + 2 = 0[/tex]

  • Taking (-x+2) to the other side

[tex] \small \sqrt{2x - 1} = x - 2 [/tex]

  • squaring both of the sides

[tex] \small 2x - 1 = {(x - 2 )}^{2} [/tex]

  • expanding the sqared binomial as ㅤㅤㅤㅤ(a-b)²= a²- 2ab + b²

[tex] \small 2x - 1 = {x}^{2} - 2 \times x \times 2 + {2}^{2} [/tex]

  • simplifying the equation

[tex] \small 2x - 1 = {x}^{2} - 4x + 4[/tex]

  • asiding the equation

[tex] \small {x}^{2} - 4x - 2x + 4 + 1 = 0\: [/tex]

[tex] \small {x}^{2} - 6x + 5 = 0\: [/tex]

  • using splitting middle term method

[tex] \small {x}^{2} - 5x - x+ 5 = 0\: [/tex]

[tex] \small x(x- 5) - (x - 5 )= 0\: [/tex]

[tex] \small (x- 1)(x - 5 )[/tex]

so the root would either be 5 or 1

_____________________________________

putting the value of x as 1,

[tex] \small \sqrt{2 \times 1 - 1} - 1 + 2 = 0[/tex]

[tex] \small 1 - 1 + 2 = 0[/tex]

[tex] \small 3 - 1≠ 0[/tex]

hence , it's not the true solution of the equation

_____________________________________

putting the value of x as 5,

[tex] \small \sqrt{2 \times 5 - 1} - 5 + 2 = 0[/tex]

[tex] \small 3 - 5 + 2 = 0[/tex]

[tex] \small 5 - 5 = 0[/tex]

[tex] \small 0 = 0[/tex]

hence ,it's the true solution of the equation

Let's solve

[tex]\\ \rm\rightarrowtail \sqrt{2x-1}-x+2=0[/tex]

[tex]\\ \rm\rightarrowtail \sqrt{2x-1}=x-2[/tex]

[tex]\\ \rm\rightarrowtail 2x-1=(x-2)^2[/tex]

[tex]\\ \rm\rightarrowtail 2x-1=x^2-4x+4[/tex]

[tex]\\ \rm\rightarrowtail x^2-6x+5=0[/tex]

[tex]\\ \rm\rightarrowtail (x-1)(x-5)=0[/tex]

  • x=1 or 2

Option B is correct

As putting 1 as x

  • √1-1+2≠0

Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.